2017
DOI: 10.4204/eptcs.256.3
|View full text |Cite
|
Sign up to set email alerts
|

On the Complexity of Model Checking for Syntactically Maximal Fragments of the Interval Temporal Logic HS with Regular Expressions

Abstract: In this paper, we investigate the model checking (MC) problem for Halpern and Shoham's interval temporal logic HS. In the last years, interval temporal logic MC has received an increasing attention as a viable alternative to the traditional (point-based) temporal logic MC, which can be recovered as a special case. Most results have been obtained under the homogeneity assumption, that constrains a proposition letter to hold over an interval if and only if it holds over each component state. Recently, Lomuscio a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…We have shown that the satisfiability problems for QCTL t X , QCTL t F and QCTL t XF are Tower-complete, and for N ≥ 2, SAT(QCTL t X,≤N ) is AExp pol -complete. Whereas AExp pol -hardness is established by reducing the alternating multi-tiling problem recently introduced in [31], the Tower-hardness of SAT(QCTL t X ) required to be able to express that a node has a number of children equal to some tower of exponentials of height k. Section V deals with the Tower-completeness of SAT(QCTL f t X ) and SAT(QCTL f t XF ), as well as Tower-completeness for the modal logics K, KD, GL, K4, D4 and S4 with propositional quantification but with adequate classes of tree-like structures. All our Tower-hardness results significantly improve what was known so far for fragments of QCTL t and for the above-mentioned well-known modal logics.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have shown that the satisfiability problems for QCTL t X , QCTL t F and QCTL t XF are Tower-complete, and for N ≥ 2, SAT(QCTL t X,≤N ) is AExp pol -complete. Whereas AExp pol -hardness is established by reducing the alternating multi-tiling problem recently introduced in [31], the Tower-hardness of SAT(QCTL t X ) required to be able to express that a node has a number of children equal to some tower of exponentials of height k. Section V deals with the Tower-completeness of SAT(QCTL f t X ) and SAT(QCTL f t XF ), as well as Tower-completeness for the modal logics K, KD, GL, K4, D4 and S4 with propositional quantification but with adequate classes of tree-like structures. All our Tower-hardness results significantly improve what was known so far for fragments of QCTL t and for the above-mentioned well-known modal logics.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of several logical problems has been captured by the class AExp pol , see e.g. [45], [20], [31]. For proving AExp pol -hardness, we use an elegant modification of Tiling 1 , introduced in [31], [32].…”
Section: Complexity Classes and Tiling Problemsmentioning
confidence: 99%
See 3 more Smart Citations